Photo-ignition process of multiwall carbon nanotubes and ferrocene by continuous wave Xe lamp illumination - Visconti, Paolo; Primiceri, Patrizio; Longo, Daniele; Strafella, Luciano; Carlucci, Paolo; Lomascolo, Mauro; Cretì, Arianna; Mele, Giuseppe (Beilstein Journal of Nanotechnology, 2017)
This work aims to investigate and characterize the photo-ignition phenomenon of MWCNT/ferrocene mixtures by using a continuous wave (CW) xenon (Xe) light source, in order to find the power ignition threshold by employing a different type of light source as was used in previous research (i.e., pulsed Xe lamp). The experimental photo-ignition tests were carried out by varying the weight ratio of the used mixtures, luminous power, and wavelength range of the incident Xe light by using selective optical filters. For a better explanation of the photo-induced ignition process, the absorption spectra of MWCNT/ferrocene mixtures and ferrocene only were obtained. The experimental results show that the luminous power (related to the entire spectrum of the Xe lamp) needed to trigger the ignition of MWCNT/ferrocene mixtures decreases with increasing metal nanoparticles content according to previously published results when using a different type of light source (i.e., pulsed vs CW Xe light source). Furthermore, less light power is required to trigger photo-ignition when moving towards the ultraviolet (UV) region. This is in agreement with the measured absorption spectra, which present higher absorption values in the UV–vis region for both MWCNT/ferrocene mixtures and ferrocene only diluted in toluene. Finally, a chemo-physical interpretation of the ignition phenomenon is proposed whereby ferrocene photo-excitation, due to photon absorption, produces ferrocene itself in its excited form and is thus capable of promoting electron transfer to MWCNTs. In this way, the resulting radical species, FeCp2+∙ and MWCNT−, easily react with oxygen giving rise to the ignition of MWCNT/ferrocene samples.
Keywords: absorption spectra; CW Xe light source; metal nanoparticle ignitors; multiwalled carbon nanotubes; photo-induced ignition